Zmartwychwstanie przez technikę. Problem tożsamości umysłu w koncepcjach rozwoju sztucznej inteligencji. - Olgierd Sroczyński (Studia Paradyskie)
In contemporary popular concepts concerning the development of artificial intelligence, it is assumed that if a program/model provides answers or operates in a manner similar to humans, then it can be considered to have achieved human-level capability. Unfortunately, such criteria are far from definitional precision, making it challenging to unequivocally determine this "human level" of artificial intelligence. Moreover, while the concept of consciousness that hypothetical artificial intelligence might attain at a human level is frequently discussed, there is a lack of reflection on the role of another element of human cognition, namely identity. However, human identity and its origins shed much light on how cognition at the human level is possible. In the article, we analyze the issue of human identity, particularly the role played by the human body in shaping it. This allows for adopting a new perspective on contemporary trends related to the development of artificial intelligence, especially the concept of "mind uploading".